Sociodemographic and clinical profile of cancer patients in the context of the COVID-19 pandemic at a University Hospital in the Northeast: cross-sectional study (Research, Society and Development, 2021)
The COVID-19 pandemic has overloaded public health services, making it a barrier to administering anti-cancer therapies. The restructuring of health services and the vulnerability of cancer patients contributed to the interruption of anticancer treatment. Thus, the objective was to describe the sociodemographic and clinical profile and main outcomes of adult and elderly cancer patients admitted to a university hospital (HU), undergoing physical therapy intervention, considering the previous and current period of the pandemic. Exploratory and retrospective study involving 71 cancer patients admitted to the HU in 2019 and 2020. Epidemiological data were collected through electronic medical records. Eligibility criteria were registration of the primary ICD related to cancer and age group (≥ 30 and ≥ 60 years). The statistical analysis considered the confounding variables: age, gender, place of residence, type of cancer, clinical outcome (discharge or death), physical therapy approaches (oxygen therapy, invasive and non-invasive mechanical ventilation) length of stay. The results demonstrate that gender was not a determining variable for hospitalization. Higher incidences of hospitalization were observed in the elderly, African descendants, patients with cancer of the colon/rectum and rectum, lung and, in equal percentage, cancers of the breast, stomach and oropharynx. Patients who required physical therapy and oxygen therapy follow-up evolved the outcome of death, regardless of the type of intervention (invasive or non-invasive mechanical ventilatory support). There was difference between the number of admissions and discharge and death outcomes in 2020 when compared to 2019.